Making Learning Fun to Educate Early Childhood Spiritual Intelligence - Zulfa, Mona Yulia; Tun, Win Ei Phyu; Arpa, Desi; Silalahi, Micha Felayati; Yudelnilastia, Yudelnilastia; Rahmanita, Rahmanita; Fillaili, Khaira (International Journal of Islamic Studies Higher Education, 2024)
The developmental aspect of spiritual intelligence is important and the most fundamental among other intelligences, as it contributes to the formation of a character with integrity, empathy and morality. The importance of developing spiritual intelligence begins at an early age, which can help children understand the values of life. This study aims to improve the spiritual intelligence of early childhood (5-6 years) through role play. This type of research is classroom action research carried out in 2 cycles of 3 meetings each cycle with research subjects totaling fifteen children consisting of six boys and nine girls. Data is collected through observation by observing and recording the symptoms that appear on the object under study and documentation is obtained through archives and documents from early childhood education institutions. The research process was carried out starting from the planning stage, action implementation, observation, and reflection. The results showed an increase in early childhood spiritual intelligence through role-playing, where in the first aspect it has reached a high level of spiritual intelligence, namely 14 people with a percentage of 93.3% in the category of developing as expected. For the second aspect, 13 children were able to behave honestly, politely, and respectfully to friends and teachers with a percentage of 86.6% in the category of developing as expected, and for the third aspect, children have self-confidence through role play obtained by 14 people with a percentage of 93.3%. The results revealed that role play is an important alternative to improve spiritual intelligence for early childhood and the results of this study can be used as initial data for subsequent researchers in studying this problem in different contexts and issues.